Innovations, difficulties, and constraints in the manufacturing of jaggery and jaggery manufacturing plants - Ukey, P D; Ingale, V M; Yenge, G B; Prathapan, K; Ghatge, J S; Patil, S B; Khot, J A (Journal of Postharvest Technology, 2022)
In India, jaggery is a popular traditional sweetener. It is produced by continuously heating and  condensing clear sugarcane juice without the use of chemicals. Currently, people are highly  conscious of the health risks associated with eating and place greater importance on food quality.  Jaggery is enriched with numerous nutrients, including vitamins, minerals, and protein. Jaggery  offers various health benefits such as blood purification, digestion regulation, beauty treatment,  improved metabolism, prevention of respiratory issues, and more. The process of making jaggery involves constant heat and mass transfer, transforming fresh  sugarcane juice into a concentrated product. The entire process includes various steps, from  sugarcane harvesting to shaping the finished product into different sizes and forms depending on its  intended use. The unit operations of jaggery processing include juice extraction, juice clarification,  boiling to concentrate juice, cooling concentrated juice, molding/shaping, drying, powdering, packing,  and storing. All of these practices, which have several drawbacks and difficulties, are employed in  traditional jaggery-making plants. The main problems and challenges that manufacturers face today  include the inferior crushing efficiency of the sugarcane crusher, the need for vast open space for  bagasse drying, labor-intensive processes, the use of various chemical and natural clarifying agents  to produce high-quality jaggery, shortened storage life, high fuel consumption, and poor thermal  efficiency. This article addresses the different concerns and problems experienced by manufacturers  and presents improvements to the plants and jaggery-making process suggested by researchers.
Keywords: Jaggery; sugarcane juice; sweetener; clarifying agents; bagasse; mechanization